Distinct differences in rates of oxygen consumption and ATP synthesis of regionally isolated non‐synaptic mouse brain mitochondria. Issue 8 (24th January 2019) - Andersen, Jens V.; Jakobsen, Emil; Waagepetersen, Helle S.; Aldana, Blanca I.
Abstract: Brain mitochondrial dysfunction has been implicated in several neurodegenerative diseases. The distribution and efficiency of mitochondria display large heterogeneity throughout the regions of the brain. This may imply that the selective regional susceptibility of neurodegenerative diseases could be mediated through inherent differences in regional mitochondrial function. To investigate regional cerebral mitochondrial energetics, the rates of oxygen consumption and adenosine‐5′‐triphosphate (ATP) synthesis were assessed in isolated non‐synaptic mitochondria of the cerebral cortex, hippocampus, and striatum of the male mouse brain. Oxygen consumption rates were assessed using a Seahorse XFe96 analyzer and ATP synthesis rates were determined by an online luciferin‐luciferase coupled luminescence assay. Complex I‐ and complex II‐driven respiration and ATP synthesis, were investigated by applying pyruvate in combination with malate, or succinate, as respiratory substrates, respectively. Hippocampal mitochondria exhibited the lowest basal and adenosine‐5′‐diphosphate (ADP)‐stimulated rate of oxygen consumption when provided pyruvate and malate. However, hippocampal mitochondria also exhibited an increased proton leak and an elevated relative rate of oxygen consumption in response to the uncoupler carbonyl cyanide 4‐(trifluoromethoxy)phenylhydrazone (FCCP), showing a large capacity for uncoupled respiration in the presence of pyruvate. When the complex II‐linked substrate succinate was provided, striatal mitochondria exhibited the highest respiration and ATP synthesis rate, whereas hippocampal mitochondria had the lowest. However, the mitochondrial efficiency, determined as ATP produced/O2 consumed, was similar between the three regions. This study reveals inherent differences in regional mitochondrial energetics and may serve as a tool for further investigations of regional mitochondrial function in relation to neurodegenerative diseases. Abstract : Brain mitochondria were isolated from the mouse cerebral cortex, hippocampus, and striatum and the rates of oxygen consumption and ATP syntheses were assessed. By applying different respiratory substrates, respiration and ATP synthesis mediated through complex I and complex II of the electron transport chain were elucidated. Several regional differences in mitochondrial function were observed, however, the rates between oxygen consumption and ATP synthesis were comparable between the regions.